1992
DOI: 10.1203/00006450-199208000-00002
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of the Circulating Antibody Secreting Cell Response in Human Diarrhea by a Human Lactobacillus Strain

Abstract: MATER IALS AND METHODScourse of diarrh ea. Maln utrition has been report ed to increase the absorption of potentially harmful antigens (2) and to impai r imm une responses (3). A poor nutrition al state may thu s increase the risk of protracted diarrh ea as well as enhance susceptibility to other infectio ns and to gastroi ntestinal allergy. The nutritio nal state of even well-no urished infants deteriorat es rapidly during diarrhea, either because of loss of appetite, deliberate withholding of oral feeds, or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
253
1
15

Year Published

1996
1996
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 616 publications
(282 citation statements)
references
References 18 publications
13
253
1
15
Order By: Relevance
“…It is noteworthy that this stimulation was without an inflammatory response, a property essential for the safe use of the strain in clinical or therapeutic applications [9,17,47]. Lactobacillus rhamnosus GG was also able to stimulate local and systemic IgA to rotavirus in children with acute rotavirus infection [32,46].…”
Section: Functional Effects Of Successful Probiotic Strainsmentioning
confidence: 98%
“…It is noteworthy that this stimulation was without an inflammatory response, a property essential for the safe use of the strain in clinical or therapeutic applications [9,17,47]. Lactobacillus rhamnosus GG was also able to stimulate local and systemic IgA to rotavirus in children with acute rotavirus infection [32,46].…”
Section: Functional Effects Of Successful Probiotic Strainsmentioning
confidence: 98%
“…Studies have demonstrated that probiotics improve gut function potentially through a number of mechanisms (1,2), including increasing epithelial barrier function (3) and modulation of the immune response (4)(5)(6). There is also evidence that probiotics can prevent colonization of the gut by pathogens.…”
mentioning
confidence: 99%
“…They inhibit potentially pathogenic bacteria, and have various immunomodulating and immunostimulating effects; they promote immune cell proliferation, enhance phagocyte activity, and increase IgA production. All this determines their potential benefits in preventing infection, particularly by intestinal pathogens, as well as bacterial translocation (95)(96)(97).…”
Section: Mechanism Of Actionmentioning
confidence: 99%